2023
DOI: 10.1002/ente.202201499
|View full text |Cite
|
Sign up to set email alerts
|

Design and Optimization of a Waste Heat Recovery Organic Rankine Cycle System with a Steam–Water Dual Heat Source

Abstract: The organic Rankine cycle (ORC) system in plants, powered by dual steam–water heat sources, has significant power generation potential and practical research value. Herein, the conditions of 700 kPa saturated steam and 650 kPa, 90 °C water heat source are considered. Four configurations of steam–water dual heat source waste heat recovery ORC systems are proposed. The independent parameters affecting the net output power of the system are obtained by developing a mathematical model and optimizing it using the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 47 publications
0
0
0
Order By: Relevance
“…Results indicated that the net power significantly raised with the expander size, which had a slight effect on the thermal efficiency of the ORC system. Employing a particle swarm optimization algorithm, Wang et al [ 21 ] studied the thermodynamic and economic models of split-flow dual- and triple-loop organic Rankine cycle systems. It was found that the triple-loop system's net power exhibited superior to that of the dual-loop system by 7.9 %.…”
Section: Introductionmentioning
confidence: 99%
“…Results indicated that the net power significantly raised with the expander size, which had a slight effect on the thermal efficiency of the ORC system. Employing a particle swarm optimization algorithm, Wang et al [ 21 ] studied the thermodynamic and economic models of split-flow dual- and triple-loop organic Rankine cycle systems. It was found that the triple-loop system's net power exhibited superior to that of the dual-loop system by 7.9 %.…”
Section: Introductionmentioning
confidence: 99%